Shallow-layer pillaring of a conductive polymer in monolithic grains to drive superior zinc storage via a cascading effect. Issue 9 (27th August 2020) - Yao, Zhenguo; Wu, Qingping; Chen, Keyi; Liu, Jianjun; Li, Chilin
Abstract : Shallow-layer pillaring of a conductive polymer activates the superior zinc storage of V2 O5 via a cascading effect. Abstract : Aqueous Zn metal batteries (ZBs) have obtained increasing attention recently owing to their low-cost and environmentally friendly nature. Unfortunately, the sluggish Zn 2+ de/intercalation in hosts often requires the nanostructural tailoring of cathode materials, which however degrades the tap density and accelerates the dissolution of active species. Herein, we propose a shallow-layer pillaring strategy to drive the superior zinc storage performance of V2 O5 monolithic grains without the prerequisite of intentional nanoscale attenuation. The in situ polymerized 3, 4-ethylenedioxythiophene chains only in the near-surface V2 O5 interlayers are sufficient to activate a cascading effect to successively open the deeper interlayers during Zn intercalation. This synergic interlayer expansion mechanism leads to a thorough and quick redox process of bulk phase V2 O5 even with micro-sized grains as opposed to the poor reaction kinetics in the non-pillared one. In contrast to excess pillaring or cation doping, the shallow-layer hybridization with a hydrophobic conductive polymer can suppress the dissolution of active species, reinforce the conductive contact between grains, lower the Zn 2+ diffusion barrier (0.39 eV) and absorption energy (0.17 eV), and upgrade the pseudocapacitance contribution (>67%) and Zn 2+ diffusion coefficient (1.43 × 10 −9 –1.81 × 10 −8 cm 2 s −1 ). This composite cathode enables an unprecedented cycling/rate performance ( e.g. 388, 367 and 351 mA h g −1 even at 5, 8 and 10 A g −1 respectively, and 269 mA h g −1 after 4500 cycles at 10 A g −1 ), corresponding to high energy densities of 280.2 and 205.8 W h kg −1 under ultrahigh power densities of 700.5 and 5960 W kg −1, respectively. This concept of shallow-layer pillaring activation (especially via rich organic molecules) can be extended to more electrode systems with the preservation of the grain integrity.